Characterization of Exotic Sorghum Germplasm Accessions for Protein, Carbohydrate Fractions and Energy Value under In Vitro Conditions - Singh, Sultan; Joshi, D. C.; Kumar, R. V.; Manjunatha, N. (Indian Journal of Animal Nutrition, 2017)
Twenty one sorghum exotic accessions with two checks CSV 15 and SSG 59-3 harvested at 50% flowering were evaluated for crude protein, carbohydrate fractions, protein fractions, digestibility, energy and in vitro methane production. Accessions differed (P